Peningkatan Kemandirian Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe Team Pair Solo Pada Siswa Kelas VIII SMP Al-Muayyad Mangkuyudan Tahun Ajaran 2014/2015 - , Masrurotun; , Drs. Slamet HW, M.Pd (2015)
Purpose of this research is to increase the independent learning of mathematics by studying cooperative model, Team Pair Solo for VIII grade students of AlMuayyad Junior High School Mangkuyudan Surakarta. The type of this research is, research for class measure that do by collaborating between researcher and 26 students. Collecting data method for this research is research method, note fieldwork, and documentation. Data analysis method for this research is data reduction, data presentation and taking summary. There are increase of independent learning of study mathematics as the result, it can be shown by the indicator : (1) There are 8 students (30,79%) whom finish their ask by independent learning before get an action and there are 20 students (76,92%) after given by an action, (2) There are 6 students (23,08%) whom can make a decision before get an action and there are 18 students (69,23%) after given by an action. (3) There are 3 students (11,54%) whom brave to ask before get an action and there are 11 students (42.31%) after given by an action. (4) There are 8 students (30,77%) whom do their group assignment cooperatively before get an action and there are 19 students (73,08%) after given by an action. Therefore, cooperative learning model Team Pair Solo can increase independent learning of study mathematics for VIII grade students of Al Muayyad Junior High School Mangkuyudan Surakarta 2014/2015.